Állami kockázatitőke-programok nemzetközi tapasztalatai - Judit Karsai (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
– Governments play several roles in the venture capital market. Based on empirical examples, the current paper focuses on the role of the government as a venture capital investor. Compared to the direct involvement of governments in investments entailing risks of market distortion, the paper demonstrates that governments increasingly contribute to the funds of the venture capital market in an indirect way: by encouraging private investors to participate. The involvement of private investors in government schemes could serve as a guarantee to select commercially viable projects without any political pressure, to schedule the financing of programs independently from election cycles, and to encourage experienced fund managers to participate in government programs. The main conclusion of the paper is that only those governmentfunded venture capital funds could ensure the proper utilization of public resources that are managed by the private sphere and are funded mostly by private investors. This would also contribute to economic policy objectives, such as improving the supply of capital for promising young companies.
Keywords: G23; G24; G28; M13; O31; 330; venture capital; private equity; government venture capital; SME finance